The Role and Significance of Pedagogy in the System of Sciences (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
If you consider any field of human education, it is carried out in connection with a certain science, it relies on the laws of that science.This article talks about the importance of pedagogy in the formation of personality and its place in the system of sciences.